Speaking Truth to Power: Kelsen, Freud, and peace through law - Schuett, Robert (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
Hans Kelsen and Sigmund Freud rank as path-breaking intellectuals and their ability to challenge the cultural status quo through social critique made them many friends, yet even more foes. Taking a fresh look at their biographical and intellectual relationship, this article recruits Kelsen as an important open society ally in today’s battles over the question of world order in international society. Rooted in what is called a sustained Freudian human nature realism in Kelsen’s international relations thinking, it is argued that a Kelsenian position of a peace through law is now as central for the social regulation of human and global affairs as it has ever been.